2005
DOI: 10.1093/humrep/dei258
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rosiglitazone and metformin on oxidative stress and homocysteine levels in lean patients with polycystic ovary syndrome

Abstract: Elevated insulin resistance, oxidative stress and plasma homocysteine levels and changes in serum lipid profile (risk factors for cardiovascular disease) were observed in lean PCOS patients. Rosiglitazone seemed to decrease elevated oxidative stress when compared with metformin treatment in lean PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 64 publications
4
101
1
1
Order By: Relevance
“…These findings, however, are highly variable and depend on the obesity status, diet and ethnicity of the population studied. Yilmaz et al found no positive impact on serum lipids in their 6 months study of PCOS patients, 9 similar to our study.…”
Section: Resultssupporting
confidence: 92%
“…These findings, however, are highly variable and depend on the obesity status, diet and ethnicity of the population studied. Yilmaz et al found no positive impact on serum lipids in their 6 months study of PCOS patients, 9 similar to our study.…”
Section: Resultssupporting
confidence: 92%
“…The increase of serum Hcy concentration in the metformin-treated patients was confirmed by a series of observational studies [16][17][18]20,25,[52][53][54][55][56]. These studies indicated that metformin was associated with an elevated concentration of serum Hcy compared with control treatment.…”
Section: Discussionmentioning
confidence: 79%
“…The dyslipidemia of PCOS is characterized by elevated plasma levels of cholesterol, low density lipoproteins (LDL), very low density lipoproteins (VLDL), and triglycerides with concomitantly reduced concentrations of high density lipoproteins (HDL) [52][53][54][55] . Homocysteine levels are also higher in women with PCOS compared to controls [56][57][58][59] , and hyperhomocysteinemia represents another independent risk factor for the development of cardiovascular disease 60 . Moderate hyperhomocysteinemia predisposes individuals to endothelial dysfunction via a mechanism involving increased oxidative stress 61 .…”
Section: Cardiovascular Risksmentioning
confidence: 99%
“…Furthermore, antioxidant reserve appears to be compromised in women with PCOS 97 . Even lean women with PCOS exhibit increased oxidative stress, as measured by levels of malonyldialdehyde, a marker of lipid peroxidation, and they have decreased serum total antioxidant levels compared to controls 56 . Recent evidence suggests that inflammatory cytokines and measures of oxidative stress, such as tumor necrosis factor-α (TNF-α) and C-reactive protein (CRP) 99,100 , may play a role in the dysregulation of the theca-interstitial compartment, and both of these factors are elevated in PCOS 97,98,101,102 .…”
Section: Pathophysiology Of Pcosmentioning
confidence: 99%